-Solid Lithium Perchlorate, a Highly Efficient and Chemoselective Catalyst for the Acetalyzation of Aldehydes (Journal of Sciences, Islamic Republic of Iran)
-A simple, efficient, and general method has been developed for the chemoselective acetalization of aldehydes with 1,3-propanediol, 1,2-ethanediol and trimethyl orthoformate in the presence of solid lithium perchlorate under solvent-free conditions. Both cyclic and acyclic acetals of aldehydes were obtained under environmentally benign conditions in good to excellent yields.